2021
DOI: 10.12968/bjon.2021.30.18.s18
|View full text |Cite
|
Sign up to set email alerts
|

Understanding female sexual dysfunction, its causes and treatments

Abstract: Female sexual dysfunction can greatly affect a woman's quality of life. Affected patients need a comprehensive assessment that includes taking a sexual history, medical evaluation and, if appropriate, a manual examination in order to diagnose, treat or identify factors relevant for each individual woman. There may be biological, psychological, emotional and relationship issues. Any biological factors such as vaginal dryness, pelvic floor dysfunction or chronic pain need to be addressed first to help prevent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In addition, we also found that in Shanghai and Nanjing, the scores or frequencies in terms of different types of sexual dysfunction were significantly higher than those in Ningxia (P < 0.05) because Shanghai and Nanjing are developed regions in China, including economic and educational 17 . Furthermore, we analyzed the factors that may affect the occurrence of FSD and found that marital status, menopause, mode of delivery, and the degree of depression and anxiety were mainly related to FSD (P < 0.05), which was similar to the results of previous studies 18 ; that is, psychological factors are an important cause of FSD. In addition, there are some other factors related to organic lesions of the external genitalia, such as mechanical damage to the pelvic floor 19 and sexual organs caused by prolonged labor during childbirth 20 , and the sexual organs, such as vaginal loss of nutrition and atrophy caused by the decline in sex hormones caused by menopause 21 , which causes damage to the normal structure of the vagina, in turn causing vaginal dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we also found that in Shanghai and Nanjing, the scores or frequencies in terms of different types of sexual dysfunction were significantly higher than those in Ningxia (P < 0.05) because Shanghai and Nanjing are developed regions in China, including economic and educational 17 . Furthermore, we analyzed the factors that may affect the occurrence of FSD and found that marital status, menopause, mode of delivery, and the degree of depression and anxiety were mainly related to FSD (P < 0.05), which was similar to the results of previous studies 18 ; that is, psychological factors are an important cause of FSD. In addition, there are some other factors related to organic lesions of the external genitalia, such as mechanical damage to the pelvic floor 19 and sexual organs caused by prolonged labor during childbirth 20 , and the sexual organs, such as vaginal loss of nutrition and atrophy caused by the decline in sex hormones caused by menopause 21 , which causes damage to the normal structure of the vagina, in turn causing vaginal dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…Diagnosing FSD may be complex due to its diverse causes, including anatomical, psychological, hormonal, or medication-induced factors. The clinician must first initiate a conversation with the patient and obtain a detailed obstetric and gynecologic medical history, including histories of sexual abuse, sexually transmitted diseases, bowel or urinary complaints, and surgeries [ 55 ]. Women who report dyspareunia may experience pain on deep penetration, raising suspicion for pathologies such as endometriosis and leiomyomas.…”
Section: Reviewmentioning
confidence: 99%
“…Note, unless the relevant questions are asked, it is not possible to know a person's sexual orientation, behaviours or gender. Finally, if a person is transgender they may have a preference for certain pronouns and, therefore, this should be ascertained 4 . The figure provides examples of questions that can be utilised to explore the various domains of sexual functioning (Figures 1 and 2).…”
Section: Formal Assessment Of Sexual Functioningmentioning
confidence: 99%
“…Finally, if a person is transgender they may have a preference for certain pronouns and, therefore, this should be ascertained. 4 The figure provides examples of questions that can be utilised to explore the various domains of sexual functioning (Figures 1 and 2 ).…”
Section: Formal Assessment Of Sexual Functioningmentioning
confidence: 99%